MatchU: An Interactive Matching Platform - Ferris, James; Hosseini, Hadi (Proceedings of the AAAI Conference on Artificial Intelligence, 2020)
MatchU is a web-based platform that offers an interactive framework to find how to form mutually-beneficial relationships, decide how to distribute resources, or resolve conflicts through a suite of matching algorithms rooted in economics and artificial intelligence. In this paper, we discuss MatchU's vision, solutions, and future directions.